The influence of synthetic and biologic matrices on the choice of the implant plane during breast reconstruction. The modern state of the problem - E. A. Baychorov; A. D. Zikiryakhodzhaev; A. Kh. Ismagilov; Yu. V. Przhedetskiy (ABV-press, 2022)
Immediately after silicone implants were described, the technique of prepectoral implant placement dominated in breast reconstructive surgery. However, this plane soon had to be abandoned due to the high frequency of complications, such as infection, capsular contracture, explantation. For these reasons, surgeons soon had to switch to the subpectoral plane. Several decades later, thanks to the discovery of synthetic and biological meshes, surgeons returned to the prepectoral plane, but at a technically new level.The purpose of this review was to analyze the role of biological and synthetic matrices as factors influencing the choice of the implant plane in one-stage breast reconstruction.